2022
DOI: 10.3389/fpls.2022.1079534
|View full text |Cite
|
Sign up to set email alerts
|

An uncharacterized gene Lb1G04794 from Limonium bicolor promotes salt tolerance and trichome development in Arabidopsis

Abstract: Halophytes can grow and reproduce in high-salinity environments, making them an important reservoir of genes conferring salt tolerance. With the expansion of saline soils worldwide, exploring the mechanisms of salt tolerance in halophytes and improving the salt tolerance of crops have become increasingly urgent. Limonium bicolor is a halophyte with salt glands that secrete excess Na+ through leaves. Here, we identified an uncharacterized gene Lb1G04794, which showed increased expression after NaCl treatment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In addition to LbRZF1 , other genes affecting salt glands have been identified. For example, overexpressing the gene Lb1G04794 with unknown function in L. bicolor resulted in an increase in the number of salt glands (Jiao et al, 2022). At the base of the L. bicolor leaf petiole, gene‐edited mutants of the transcription factor gene LbNAC4 produced only two or three foci compared with the normal four fluorescent foci seen in the WT; conversely, the salt glands of lines overexpressing LbNAC4 had six foci and increased salt gland density (Zhao et al, 2023a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to LbRZF1 , other genes affecting salt glands have been identified. For example, overexpressing the gene Lb1G04794 with unknown function in L. bicolor resulted in an increase in the number of salt glands (Jiao et al, 2022). At the base of the L. bicolor leaf petiole, gene‐edited mutants of the transcription factor gene LbNAC4 produced only two or three foci compared with the normal four fluorescent foci seen in the WT; conversely, the salt glands of lines overexpressing LbNAC4 had six foci and increased salt gland density (Zhao et al, 2023a).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several genes from L. bicolor result in greater salt tolerance when heterologously expressed in Arabidopsis. For example, overexpression of Lb1G04794 in Arabidopsis represses root hair development and increases salt tolerance (Jiao et al, 2022). Overexpression of Lb1G04202 increases tolerance to salt during the germination of transgenic Arabidopsis (Wang et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…As for Lb1G04794, it was only the phenotype associated with salt glands that was analyzed in the 35S::Lb1G04794 L. bicolor. The further function of Lb1G04794 in salt stress was analyzed in detail in Arabidopsis [13]. These results indicate that functional analyses of genes of interest have still been carried out via heterologous expression in Arabidopsis.…”
Section: Introductionmentioning
confidence: 89%
“…Overexpression of Lb1G04202 in Arabidopsis resulted in increased salt tolerance by promoting proline biosynthesis [12]. When an uncharacterized gene Lb1G04794 was overexpressed in Arabidopsis, transgenic Arabidopsis showed that the number of trichomes was increased, root hairs were decreased, and salt resistance was enhanced [13]. Overexpression of an R1-type MYB transcription factor LbMYB48 in Arabidopsis has been shown to increase salt tolerance through maintaining ion and osmotic balance and might be involved in the abscisic acid signaling pathway [14].…”
Section: Introductionmentioning
confidence: 99%